Resisting militarism direct action and the politics of subversion - Rossdale, Chris (Advances in critical military studies, 2019)
In the past 15 years, UK anti-militarist activists have auctioned off a tank outside an arms fair, superglued themselves to Lockheed Martin's central London offices and stopped a battleship with a canoe. They have also challenged militarism in many other everyday ways. This book explores why anti-militarists resist, considers the politics of different tactics and examines the tensions and debates within the movement. As it explores the multifaceted, imaginative and highly subversive world of anti-militarism, the book also makes two overarching arguments. First, that anti-militarists can help us to understand militarism in new and useful ways. And secondly, that the methods and ideas used by anti-militarists can be a potent force for radical political change.